The Dynamics of Demotivation and Remotivation Among Chinese Students in Learning English: Insights from a Q Methodology Study - Yanhong Ma (SAGE Open)
Research on language motivation has tended to focus on the phenomena of demotivation and remotivation in the English classroom. This study utilized Q methodology to analyze the dynamics of demotivation and remotivation among 15 Chinese university students during their English learning process from primary school to senior middle school. Informed by the complex dynamic systems theory (CDST), the study aims to examine factors that demotivate and remotivate Chinese learners of English, as well as depict the characteristics of demotivation and remotivation in motivation development. The results showed that individuals who tended to develop their ideal L2 selves were better able to cope with demotivating situations and more likely to regain motivation. Conversely, those with an ought-to L2 self were more likely to become demotivated over time and developed a fixed mindset, although they could occasionally be motivated again by certain factors. The study findings suggest that a comprehensive and dynamic self-system can be utilized to investigate demotivation and remotivation in English learning. In the end, the pedagogical implications of teaching and learning English are discussed.